Utilizing Organic Waste to Enhance Science Skills in Early Childhood - Lathifah, Ilhammatul; Reni Pawestuti Ambari Sumanto (Jurnal Pendidikan Anak Usia Dini Undiksha, 2025)
The low level of science skills among early childhood learners is caused by the science learning strategies applied by teachers, which tend to be monotonous and rely heavily on books or magazines. Children need to be given opportunities to learn about science and explore their surroundings so they can observe and directly experience what they are learning. Therefore, the purpose of this study is to analyze the improvement of science skills in early childhood through the implementation of organic waste utilization activities. This study is a pre-experimental research using a one-group pretest and posttest design. The population in this study consists of all early childhood students in a PAUD (Early Childhood Education Institution). The selected sample included 37 children. The sample was chosen using a purposive sampling technique, where the selection was based on specific considerations. Data collection was conducted through observation using research instruments. The collected data were analyzed in two stages: normality testing and hypothesis testing. The data analysis method used to test the hypothesis was the Paired Sample T-test. The results showed that the average score of children's science skills through the application of organic waste utilization activities increased from 56.30 in the pretest to 104.92 in the posttest, with a significance value of 0.000 < 0.05. Therefore, it can be concluded that the science skills of early childhood learners improved after the implementation of organic waste utilization activities.